The Content Form of the Lexeme “Average”: Synchrony and Diachrony - Tatiana A. Svetonosova (Vestnik MGIMO-Universiteta, 2015)
Why can a word in the English language have various meanings? As a rule, such queries arise in English for General Purposes classes and their number is increasing in English for Specific Purposes classes. The word average is learnt in both above-mentioned classes and it is evident that it has different meanings. It is worth noting that not all these meanings can be found in monolingual dictionaries. Watching the usage of the word average while teaching has led to the given article. The synchronic and diachronic analysis of the content form of the lexeme average as the noun is conducted in the article. The theoretical part embraces points of semantics development, lexical semantics notions as well as concepts and definitions of semantics terms used in this article. Then the reasons for choosing the lexeme average are stated, the goal of the article is set, the research methods are provided. The practical part covers the synchronic and diachronic contexts in which the lexeme average operates - data from the British National Corpus, entries from monolingual dictionaries, materials from coursebooks, entries from etymological dictionaries. All these contexts are analyzed and inferences about the content form of the lexeme average are made. At the end of the article further possible research of the lexeme average is outlined.